Chondrinema litorale gen. nov., sp. nov., of the phylum Bacteroidota, carrying multiple megaplasmids isolated from a tidal flat in the West Sea, Korea - Muhammad, Neak; Avila, Forbes; Lee, Yong-Jae; Han, Ho Le; Kim, Kyoung-Ho; Kim, Song-Gun (Frontiers in Marine Science, 2023)
A Gram-stain-negative, long rod, oxidase and catalase-positive strain WSW3-B12T was isolated from red algae on tidal flats in the West Sea, Korea. Phylogenetic analysis based on the 16S rRNA gene sequence revealed that the strain WSW3-B12T had the highest sequence similarity, 92.7%, to Flexithrix dorotheae DSM 6795T, followed by Rapidithrix thailandica TISTR 1750T at 90.8% in the family Flammeovirgaceae of the phylum Bacteroidota. The whole genome sequence determined using both the Nanopore and Illumina platforms revealed that the complete genome consists of 29 contigs, among which contig 1 was a circular chromosome, while the remaining 28 contigs were plasmids. The size of the genome was 10.1 Mbp and the G+C content was 34.1%. The average nucleotide identity (ANI), digital DNA–DNA hybridization (dDDH), average amino acid identity (AAI), and percentage of conserved proteins (POCP), phylogenomic-related indexes between the strain WSW3-B12T and the closest strain Flexithrix dorotheae DSM 6795T, were 76.6%, 19.9%, 57.2%, and 55.6%, respectively, which were all lower than the threshold values to support the creation of a novel genus. A comprehensive genome analysis revealed that the strain WSW3-B12T harbored many of the key genes involved in central metabolism in the main chromosome and also carried important genes for the production of vitamins, quinone, and antimicrobial resistance on the plasmids. The strain also carried genes that are involved in the metabolism of heavy metals such as arsenic, cobalt, copper, and iron on both the chromosome and plasmids. Furthermore, the genome of the strain was highly enriched with carbohydrate-active enzymes (CAZymes), carrying a total of 238 CAZymes. Moreover, a complete CRISPR/Cas system was detected on plasmid 19. The major fatty acids of the strain were iso-C15:0 and C16:1 ω5. The polar lipids contained phosphatidylethanolamine, four unidentified lipids, and four glycolipids. The respiratory quinone was menaquinone 7. Based on the phenotypic, chemotaxonomic, and genomic analyses, the strain WSW3-B12T could be assigned to a novel species and novel genus within the family Flammeovirgaceae, for which the name Chondrinema litorale gen. nov., sp. nov. (type strain WSW3-B12T = KCTC 82707T = GDMCC 1.3198T) is proposed.